2010
DOI: 10.1186/1758-907x-1-15
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous F-box protein regulates ARGONAUTE1 in Arabidopsis thaliana

Abstract: ARGONAUTE1 (AGO1) mediates microRNA- and small interfering RNA-directed posttranscriptional gene silencing in Arabidopsis thaliana. Mutant alleles of SQUINT (SQN) slightly reduce AGO1 activity and have weak effects on shoot morphology. A screen for mutations that suppress the sqn phenotype produced loss-of-function mutations in the F-box gene FBW2. Mutations in FBW2 not only suppress sqn but also suppress many of the developmental phenotypes of weak, but not null, alleles of AGO1 by increasing AGO1 protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 40 publications
10
69
0
Order By: Relevance
“…1E). It is noteworthy that in the absence of P0, AGO1 also precipitates CUL1, although less efficiently, suggesting that endogenous SCF-type ubiquitin E3 ligases may also regulate AGO1 as recently proposed (17). Furthermore, we observed an enrichment of polyubiquitin conjugates in AGO1 immunoprecipitates in the presence of P0.…”
Section: Resultssupporting
confidence: 64%
“…1E). It is noteworthy that in the absence of P0, AGO1 also precipitates CUL1, although less efficiently, suggesting that endogenous SCF-type ubiquitin E3 ligases may also regulate AGO1 as recently proposed (17). Furthermore, we observed an enrichment of polyubiquitin conjugates in AGO1 immunoprecipitates in the presence of P0.…”
Section: Resultssupporting
confidence: 64%
“…After growing on Murashige and Skoog (MS) medium containing 30 mM ABA for 5 d, the root length of ago1-27 and the two 35S:MIR168a lines decreased 85%, 70%, and 75%, respectively, compared with a 40% decrease in wild-type plants. These results indicate that disturbance of AGO1 function leads to enhanced sensitivity to exogenous ABA treatment and are consistent with the results of Earley et al (2010).…”
Section: Resultssupporting
confidence: 81%
“…Although several AGO proteins have been shown to regulate biotic stresses (Katiyar-Agarwal et al, 2007;Li et al, 2010;Zhang et al, 2011), the role of AGO proteins in regulating abiotic stress responses is still not well understood. A recent report showed that a decrease in AGO1 confers hypersensitivity to ABA, whereas an increase in the level of AGO1 leads to ABA hyposensitivity (Earley et al, 2010). However, the role of AGO1 in abiotic stress response pathways is still unclear.…”
mentioning
confidence: 99%
“…Moreover, recent work showed that mutations in the F-box protein FBW2 suppress sqn mutations as well as hypomorphic ago1 mutations. In addition, overexpression of FBW2 reduces AGO1 protein levels but not AGO1 mRNA levels, suggesting that FBW2 acts as a negative regulator of AGO1 (Earley et al, 2010).…”
Section: Posttranslational Regulation Of Ago Proteinsmentioning
confidence: 99%